From waste to value: protein hydrolysates from byproducts of the Argentine hake (Merluccius hubbsi) processing using endogenous enzymes and Alcalase® 2.4L - Clara Liebana; Nair de los Ángeles Pereira; Analia Fernández-Gimenez; Maria Florencia Fangio (Marine and Fishery Sciences)
The valorization of fishery byproducts is essential to reduce waste and create high-value products. Waste from Argentine hake (Merluccius hubbsi) could enhance its functional and antioxidant properties through hydrolysis, releasing peptides with bioactive properties. Protein hydrolysates of Argentine hake were produced through autolysis (Aut) and enzymatic hydrolysis using Alcalase® 2.4L at concentrations of 0.24% and 2% (v/v) (Alc-0.24 and Alc-2), respectively, over 150 min. Alkaline peptidase activity, degree of hydrolysis, and antioxidant activity were assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radical ABTS·+ scavenging assays. All hydrolysates retained alkaline peptidase activity throughout the process. Alcalase-treated hydrolysates exhibited significantly higher peptidase activity and hydrolysis degree compared to autolysis. At 60 min, Alc-0.24 reached peptidase activity levels similar to Alc-2, and by 30 min, both had comparable degrees of hydrolysis. ABTS·+ scavenging activity increased over time for Alc-0.24, with both Alcalase® 2.4L concentrations outperforming autolysis. No significant differences were found between Alc-0.24 and Alc-2. Although all hydrolysates showed DPPH scavenging activity, no significant differences were detected between treatments or reaction times. These findings highlight the potential for producing value-added protein hydrolysates from Argentine hake waste.